A Nanogel with Effective Blood-Brain Barrier Penetration Ability through Passive and Active Dual-Targeting Function. (24th December 2021) - Liu, Jun; Li, Meng; Huang, Yong; Zhang, Li; Li, Wei; Cao, Peng; Min, Weijie; Li, Jingyuan; Jing, Wei
Abstract : Clinically, surgery assisted by chemotherapy is the most effective treatment of cancer. But from our clinical observation, the median survival of patients with glioblastoma is still not so good with only 15-16 months. The low therapeutic index is mainly due to the blood-brain barrier (BBB) which significantly hindered the chemotherapeutic drug accumulation in tumor tissue. One main composition of the BBB is astrocyte, which contains a lipophilic cell membrane, which prevents more than 98% of small-molecule drugs from entering the brain. Previously, we found that the nanogel with passive targeting function can increase the BBB penetration ability, which indicates that it could be used to overcome the above mentioned in vivo obstacles which promoted drug accumulation in the tumor. In this study, thermosensitive targeted nanogel delivery systems (DPPC) with cell-penetrating peptides (CPP) are introduced onto the particle surface for active astrocyte breaking. The hydrodynamic radius of DPPC is around 300 nm, the potential is about 0-5 mV, and the TEM and DLS studies further confirm its well spherical morphology and uniform distribution. The DPPC is verified as the biocompatible carriers for further application by cell viability tests. The in vitro -constructed BBB model successfully proves that DPPC can efficiently penetrate the BBB, which is attributed to both the temperature-sensitive passive targeting and the active CPP penetration. Consequently, the intracellular doxorubicin (DOX) promotes such functional DPPC at the relatively high temperature inside tumor microenvironment (TME) ( 42°C), which obviously improves intratumor drug accumulation and tumor cell-killing effects. The dual-targeted nanogel delivery systems designed in this study provides a more effective strategy for the treatment of glioma.